2022
DOI: 10.3389/fnagi.2022.854758
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Hypointensity of Middle Cingulate Gyrus and Thalamus in Age-Related Macular Degeneration Patients: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: ObjectiveAge-related macular degeneration (AMD) causes visual damage and blindness globally. The purpose of this study was to investigate changes in functional connectivity (FC) in AMD patients using resting-state functional magnetic resonance imaging (rs-fMRI).Subjects and MethodsA total of 23 patients (12 male, 11 female) with AMD were enrolled to the AMD patients group (AMDs), and 17 healthy age-, sex-, and education-matched controls (9 male, 8 female) to the healthy controls group (HCs). All participants u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Our findings of accelerated FA reduction in visual, temporal, and cingulate areas complement reports of altered functional connectivity [82,93] in the cingulate, and its altered role in memory related tasks in AMD [37]. Damage in both the anterior and posterior cingulate has been associated with apathy, akinesia, and increased stupor [94].…”
Section: Discussionsupporting
confidence: 80%
“…Our findings of accelerated FA reduction in visual, temporal, and cingulate areas complement reports of altered functional connectivity [82,93] in the cingulate, and its altered role in memory related tasks in AMD [37]. Damage in both the anterior and posterior cingulate has been associated with apathy, akinesia, and increased stupor [94].…”
Section: Discussionsupporting
confidence: 80%
“…The middle cingulate gyrus (MCG) is located between the cingulate sulcus and the sulcus of the corpus callosum and has extensive connections with other parts of the brain through nerve fibers ( Li et al, 2017 ; Huang et al, 2018 ). The MCG is regarded as a significant part of the emotional circuit and participates in processes such as regulating the body’s cognitive, emotional, memory, and self-evaluation functions ( Xiao et al, 2022 ). Recently, an increasing number of studies have reported that the cingulate cortex is widely related to the development of depression.…”
Section: Discussionmentioning
confidence: 99%